A PHILOSOPHICAL STUDY OF CREATIVE STAGE HOUSES FOR MARGINALIZED PEOPLE - Nurul Qolby Irbani Tenriola; Sri Handayani (Journal of Development and Integrated Engineering, 2021)
AbstractThe Creative Stage House for the Marginal is an architectural design which is the result of an architectural design competition for housing. Intended for the marginalized, this house is designed with a behaviorial approach and the Sundanese cultural architecture which is the location of its design research. The purpose of this article is to identify and describe the principles and characteristics of traditional Sundanese architecture that are the background in the design and to understand the principles and characteristics of the application of traditional Sundanese architecture in the design of the Creative Stage House for the Marginal. The research method used is descriptive qualitative which is expected to be able to describe the application of the traditional architectural form of Sundanese culture to the design of the house through literature study. By identifying the visual characteristics of the spatial form of the Creative Stage House for the Marginal, it is known that the architectural design of the Creative Stage House for the Marginal adapts not only the form of Sundanese architecture but the values contained in it such as the concept of dividing the three masses of the house building. The results of this philosophical study found that the composition of the masses, the typology of buildings that adhere to Sundanese cosmology and the shape of the roof that uses the Sundanese Julang Apak architecture hold the hope of increasing the standard of living and self-confidence of the marginalized. Keywords: Philosophy, Sundanese Traditional House, Traditional Architecture